A snapshot of the predominant single nucleotide polymorphism cluster groups of Mycobacterium tuberculosis clinical isolates in Delhi, India. (September 2016) - Varma-Basil, Mandira; Narang, Anshika; Chakravorty, Soumitesh; Garima, Kushal; Gupta, Shraddha; Kumar Sharma, Naresh; Giri, Astha; Zozio, Thierry; Couvin, David; Hanif, Mahmud; Bhatnagar, Anuj; Menon, Balakrishnan; et al.
Summary: Several attempts have been made to associate phylogenetic differences among Mycobacterium tuberculosis strains to variations in the clinical outcome of the disease and to drug resistance. We genotyped 139 clinical isolates of M. tuberculosis obtained from patients of pulmonary tuberculosis in North Delhi region. The isolates were analyzed using nine Single nucleotide polymorphism (SNP) markers, spoligotyping and MIRU-VNTRs; and the results were correlated with their drug susceptibility profile. Results of SNP cluster group (SCG) analysis (available for 138 isolates) showed that the most predominant cluster was SCG 3a, observed in 58.7% (81/138) of the isolates with 44.4% (36/81) of these being drug susceptible, while 16% (13/81) were multidrug resistant (MDR). Of the ancestral cluster SCG 1 observed in 19.5% (27/138) of the isolates, 14.8% (4/27) were MDR while 44.4% (12/27) were drug susceptible. SCG 2 formed 5.79% (8/138) of the isolates and 50% (4/8) of these were multidrug resistant (MDR). Spoligotyping subdivided the strains into 45 shared types (n = 125) and 14 orphan strains. The orphan strains were mostly associated with SCG 3a or SCG 1, reflecting the principal SCGs found in the Indian population. SCG 1 and SCG 2 genotypes were concordant with the East African Indian (EAI) and Beijing families respectively. Central Asian (CAS) clade and its sublineages were predominantly associated with SCG 3a. No consistent association was seen between the SCGs and Harlem, T or X clades. The 15 loci MIRU-VNTR typing revealed 123/136 isolates to be unclustered, while 13 isolates were present in 6 clusters of 2–3 isolates each. However, correlating the cluster analysis with patient details did not suggest any evidence of recent transmission. In conclusion, though our study revealed the preponderance of SCG 1 and 3a in the M. tuberculosis population circulating in the region, the diversity of strains highlights the changes occurring within lineages and reemphasizes the importance of cluster investigations in extended studies.